Biomethanization of yeast, bran and sewage sludge generated by a ethanol fermentation industry in the jungle of Peru - Cruz Pinares, Ramiro Rufino (2024)
The treatment of industrial effluents with a high content of organic matter is one of the main challenges currently faced by the ethanol fermentation industry, generating different types of waste and its inadequate disposal can cause negative effects on the environment, including greenhouse gas emissions. greenhouse effect, as an agro-industrial, has the possibility of being used in energy production, through the production of biogas. This study investigates the potential for biomethanation of waste yeast supernatant (RSL), bran (RA) and sludge (RL) using anaerobic digestion technology at mesophilic temperature. The waste was collected from a beer production industry located in the Peruvian jungle. The accumulated biogas productions were 659.33 mL/g SV for RSL, 612.72 mL/g SV for RA, and 691.71 mL/g SV for RL. Regarding the concentration of methane in the biogas, the values were 58.47% for RSL, 56.56% for RA and 60.94% for RL. The results obtained in the present research demonstrate that the problem of waste in the brewing industry can be effectively converted into an environmentally friendly solution for the production of biogas using the Anaerobic Digestion process, and is also a reference for other industries similars.